Development of a blockchain-based website application for storing certificate (Case study at Universitas Sultan Ageng Tirtayasa) - Bahauddin, Achmad; Ferdinant, Putro Ferro; Elisabeth, Devalia; Ruwani, Tanti (Universitas Sultan Ageng Tirtayasa, 2023)
Universitas Sultan Ageng Tirtayasa currently lacks a secure application to store digital certificates, including diplomas and academic transcripts, with an assurance of non-alteration. Consequently, a research study was conducted to develop a blockchain-based certificate storage on its website. The choice of blockchain technology was driven by its cryptographic security, immutability, distributed ledger, and decentralized features. The research aimed to identify stakeholder needs for website application development, design a blockchain-based website application for storing certificates, and assess the outcomes of testing this application. The research followed the System Development Life Cycle (SDLC) method, encompassing planning, analysis, design, implementation, and system testing stages. The stakeholders involved in this website application included university administrators responsible for uploading digital certificates, students accessing their own certificates, and companies verifying student credentials. The application was designed with rich images, use case diagrams, sequence diagrams, hierarchical charts, entity-relationship diagrams, and application specifications. The results of the System Usability Scale testing showed a score of 76.56, indicating that the application falls within the acceptable range and is deemed acceptable by users.